Improvement on Diesel Conversion of HydroDeOxygenation Nyamplung Oil by Multi Stage H2 - Joni Prasetyo; Galuh Wirama Murti; Sumbogo Murti SD; Adiarso .; Gina Taspiah; Yulianti Christina; Fadlillah Akbar (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Nyamplung (Calophyllum inophyllum L.) has a high survival potency in wide variety environment, fruitingall year round and easy regeneration. Nyamplung oil is the most suitable raw material as feedstock of biofuelbecause of its high yield of the seeds and in utilization not compete with food interests. Utilization nyamplungoil for Green Diesel through two basic stages, processing into Pure Plant Oil (PPO) and PPO upgradinginto Green Diesel. PPO upgrading with target Green Diesel further divided into two stages:Hydrodeoxygenation (HDO) and isomerization. In this preliminary study, PPO upgrading is only carried outby HDO only using NiMo catalyst. HDO is done in batch processes to identify the characteristics of theprocess at a temperature of 300oC, bar and the 5% catalyst. Meanwhile, to increase the nyamplung oilconversion into diesel, then the multi-stage Hydrogen (H2) was done in the process. Stage number of H2inserting is the major parameter in this HDO process. In the multi-stage H2: 1 times, 2 times and 4 times intothe reactor. Multi-stage H2 is done by replacing the H2 gas into the reactor, after a process gas frompreviously discarded. Carboxilation and carbonilation occurs in HDO process. By multi-stage H2, it showedan increasing yield of diesel conversion. From 1x stage H2 inserting to 2x and 4x stages of H2, it improve theyield from 0.32% to 0.76% and to 1.3%. This shows that the yield HDO is determined largely by theeffectiveness of H2 and PPO contact with the catalyst therein. Unfortunately, this condition is very difficult tobe achieved at a high pressure batch reactor. Further testing is doing HDO in a continuous reactor andobtained the conversion reached a yield of 50.48%.